(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
As the world is developing globally, people’s needs are increasing day by day, communication tools are developing, as a result, the people of the world are getting closer to each other. Their closeness is reflected not only in communication, but also in lifestyle, culture, social and personal life, language, religion, business, development and even food. Today, regardless of where we are in the world, there is a tool that connects us firmly and has eliminated thousands of kilometers. This important discovery is called "social media" in modern parlance. This article describes social media, the definitions given to it by several scientists, the functional blocks that make it up, and the functions of these functions on the platform.